Banking Crises and Bank Rescues: The Effect of Reputation. - Corbett, J; Mitchell, J (2000)
This paper focuses on bank rescue packages and on the behaviour of troubled banks in light of rescue offers. A puzzling feature of experience with banking crises is that in many cases policy authorities make offers of bank rescue, and banks are reluctant to accept these offers. We study situations in which regulators have decided to offer bank rescue plans, and we show that a combination of factors, including bankers' reputational concerns can explain banks' potential reluctance to accept offers of recapitalisation.